Manufacturer Cartels and Resale Price Maintenance - Matthias Hunold (ZBW - Leibniz Information Centre for Economics, 2020)
We provide a theory of how RPM facilitate upstream cartels absent any information asymmetries using a model with manufacturer and retailer competition. Because retailers have an effective outside option to each manufacturer's contract, the manufacturers can only ensure contract acceptance by leaving a sufficient margin to the retailers. This restricts the wholesale price level even when manufacturers collude. In this context, resale price maintenance may only be profitable for the manufacturers if they collude. We thus provide a novel theory of harm for resale price maintenance when manufacturers collude and illustrate the fit of this theory in various competition policy cases.
Keywords: L41; L42; L81; 330; resale price maintenance; collusion; retailing